Masyarakat Tradisi Islam Melayu Jambi: Perspektif Pierre Bordieau - Aliyas, Aliyas (Rihlah: Jurnal Sejarah dan Kebudayaan, 2020)
Malay was the first kingdom to control Jambi. Jambi City was historically known as one of the centers of the Malay Kingdom. Chinese records mention that Malays in Jambi during the T'ang Dynasty called Mo-lo-yu I Tsing. Jambi Malay Islam as research in the context of the Islamic tradition community with Pierre Bordieau's view. This study uses a literature review, by conducting a literature study with the method of collecting library data, using a historical approach to reconstruct the Jambi Malay Islamic tradition community as a Malay Islamic identity in Indonesia. Melayu merupakan kerajaan pertama yang menguasai Jambi. Secara historis Kota Jambi dikenal sebagai salah satu pusat Kerajaan Melayu. Catatan Tiongkok menyebutkan bahwa Melayu di Jambi pada zaman Dinasti T’ang menyebut Mo-lo-yu adalah I Tsing. Islam Melayu Jambi sebagai penelitian dalam konteks masyarakat tradisi Islam dengan pandangan Pierre Bordieau. Penelitian ini memakai kajian literatur, dengan melakukan studi kepustakaan dengan metode pengumpulan data pustaka, menggunakan pendekatan sejarah untuk merekonstruksi masyarakat tradisi Islam melayu Jambi sebagai identitas Islam melayu di Indonesia.